Calcaneus fractures: An evaluation of the quality and reliability of online resources. (December 2021) - Patel, Arpit; Aljabi, Yasser; Ray, Pinak
Highlights: Calcaneal fractures are destructive injuries that can have severe implications on quality of life. It is essential that good quality information is readily available for patients in order to guide management. Online health information can be assessed using the DISCERN tool, JAMA Benchmark criteria and HON-code certificate. A novel Calcaneus Fracture Specific Content Score (CFSCS) can evaluate information on these debilitating injuries. Abstract: Aim: To evaluate the reliability and quality of only resources available online on Calcaneal fractures. Methods: 70 websites were identified using the search term 'Calcaneus fractures'. Google, Yahoo! and Bing were the three major search engines used for the study. Websites were classified by type and assessed for reliability and readability by means of DISCERN score, Journal of the Medical Association ( JAMA ) benchmark criteria and the presence or absence of HON-Code certification. In addition, a Calcaneus Fracture Specific Content Score (CFSCS) was designed in conjunction with two speciality trained foot & ankle surgeons in order to gauge content quality itself. Results: Academic websites made up the majority of URLs that were identified followed by Physician and Commercial. Overall mean DISCERN and JAMA scores were 49.8 (range 16–64) and 2.1 (range 0–4) respectively. Mean CFSCS was 18.3 (range 0–25). 30 of the total websites were HON-code certified. There was a statistically significant correlation identified between presence of HON-code certificate and DISCERN, JAMA and novel CFSCS (p < 0.001). Conclusion: There is an increasing tendency for patients to peruse online resources to understand their injuries and management options. This is particularly true for the younger cohort of patients in whom Calcaneus fractures occur more commonly. One must understand the varying quality of information available online in order to appropriately direct patients to areas of higher quality and reliability.